Treatment-emergent Affective Switch: A Case Series Study - Jesvin L Johnson; M Shashwath Sathyanth; Anil Kakunje (Indian Journal of Private Psychiatry)
Introduction: Bipolar disorder is a widespread psychiatric condition characterized by mood swings, impacting millions worldwide. It includes subtypes such as bipolar I and bipolar II, with differing manic and depressive episode patterns. Treatment encompasses medication, psychotherapy, and psychosocial interventions. Managing antidepressant use in bipolar disorder is crucial due to the risk of the treatment-emergent affective switch (TEAS), where antidepressants can induce shifts from depression to mania or hypomania, a complex phenomenon influenced by genetics, neurobiology, and environment. Atypical antipsychotics offer promise as mood stabilizers and TEAS risk reducers. Patient factors such as age, gender, and illness history also influence TEAS susceptibility. Recognizing and addressing TEAS is vital in clinical practice to prevent symptom exacerbation and functional impairment. In this case series, we delve into TEAS among bipolar patients receiving antidepressant treatment, aiming to deepen comprehension, enhance patient care, and inform future research. Methods: This study includes nine cases obtained from a tertiary care center, with a focus on six selected cases diagnosed with bipolar affective disorder and TEAS as per the International Classification of Diseases, Tenth Revision (ICD-10) criteria. Case selection involved extensive interviews, data collection from hospital records, and discussions with treating psychiatrists. Consent was obtained and privacy was maintained. Demographic, social, and clinical information is presented, offering a comprehensive overview of the cases. These data provide insights into the occurrence and management of TEAS in bipolar affective disorder. Detailed case information can be found in the tables.